Clarification and concentration of oligosaccharides from artichoke extract by a sequential process with microfiltration and nanofiltration membranes. (July 2016) - Machado, Mariana T.C.; Trevisan, Susane; Pimentel-Souza, Jane D.R.; Pastore, Glaucia M.; Hubinger, Miriam D.
Abstract: Artichoke solid waste is considered a cheap fructooligosaccharides source. The extract from this material contains suspended solids, macromolecules and prebiotic sugars. The prebiotic sugars need to be clarified, purified and concentrated to increase its value. In this study, we evaluated the technical feasibility of sequential microfiltration (to clarify the artichoke extract) and nanofiltration (to purify and concentrate the prebiotic sugars). The investigation was carried out in laboratory scale, using different microfiltration and nanofiltration membranes subjected to different operation pressures. Microfiltration was able to clarify the extract with almost 100% of prebiotic sugars recovered in permeate. Microfiltration processes presented flux decline (the final flux was between 60 and 80% of the initial one) caused by cake layer formation, as observed by surface analysis. The membrane that presented the lowest flux decline and less solids deposition on its surface (polyethersulfone with a pore size of 0.05 μm), had its permeate subjected to nanofiltration. In this last step, 100% of retention of prebiotic sugar was obtained, mainly using polyamide membrane with molecular weight cut off of 150–300 Da. The sequential process allowed to produce a concentrate fraction can be used as an ingredient on foodstuff applications. Highlights: Extract from artichoke industrial solid waste is rich in fructooligosaccharides. Permeate flux, membrane fouling and extract quality were analyzed for microfiltration. Artichoke waste extract was successfully clarified by microfiltration process. The concentrate from nanofiltration process showed high oligosaccharide content. Concentrated artichoke waste extract can be a functional ingredient in food industry.